Zeleni prehod in trajnostni razvoj - Tomažič, Luka Martin (Podjetje in delo, 2022)
With public policies related to the green transition, the European Union and its member states seek a balance between environmental protection and development efforts. Following the Brundtland understanding of inter-generational and intra-generational solidarity, human beings are placed in the foreground. This contribution is intended to highlight possible approaches that can be used to achieve the green transition at the intersection of energy and environmental protection effectively and in a socially beneficial way. The aim is not to find definitive solutions, especially considering the extreme variability of social environments in the light of climate change, but merely to point out possible public policy approaches that can complement the state's traditional regulation and legislative activities. The inclusion of complementary soft-paternalistic and even deregulatory practices can significantly contribute to fulfilling public policy goals in the energy and environmental protection field. Changes at the level of legislation are not enough. To achieve a green transition, an adjustment of values is necessary.
Keywords: dregljaji; pravo energetike; regulacija; trajnostni razvoj; zeleni prehod